2015
DOI: 10.1182/blood-2014-08-588442
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous plasminogen activators mediate progressive intracerebral hemorrhage after traumatic brain injury in mice

Abstract: Key Points Closed head trauma sequentially releases tPA followed by uPA from injured brain. Increased uPA is responsible for delayed intracerebral hemorrhage, which is prevented by a tPA variant that inhibits uPA activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 50 publications
2
115
1
Order By: Relevance
“…70 As expected, uPA and tPA knockout mice had reduced intracranial hemorrhage (ICH) after TBI compared with wild type, whereas PAI-1 knockout mice had worse ICH. As mentioned earlier, CSF and brain parenchyma levels of tPA peaked several hours before uPA levels; in this context, early TXA reduced ICH, whereas late TXA exacerbated it.…”
Section: Trauma-induced Coagulopathy 1045mentioning
confidence: 80%
See 1 more Smart Citation
“…70 As expected, uPA and tPA knockout mice had reduced intracranial hemorrhage (ICH) after TBI compared with wild type, whereas PAI-1 knockout mice had worse ICH. As mentioned earlier, CSF and brain parenchyma levels of tPA peaked several hours before uPA levels; in this context, early TXA reduced ICH, whereas late TXA exacerbated it.…”
Section: Trauma-induced Coagulopathy 1045mentioning
confidence: 80%
“…One explanation may be the differential effect of TXA on tPA-vs uPA-mediated fibrinolysis combined with time-varying expression of these plasminogen activators: although the TXA-induced conformational change on plasminogen reduces tPA-mediated activation, it actually accelerates uPA-mediated activation, 69 and Hijazi et al recently demonstrated in a mouse model of isolated TBI that cerebrospinal fluid (CSF) and brain parenchyma levels of tPA peaked within 3 hours, whereas uPA levels peaked at 8 hours: after tPA levels had already decreased. 70 Although this finding plausibly explains the time-dependent effect of TXA on bleeding in CRASH-2, confirmation is required in human studies.…”
Section: Trauma-induced Coagulopathy 1045mentioning
confidence: 99%
“…In isolated TBI without major bleeding, brain-derived TF-induced consumptive coagulopathy 129 and the release of plasminogen activators result in local and systemic fibrinolysis, intracerebral hemorrhage and the development of acute traumatic coagulopathy 130 . In addition, after TBI, the complement system has been shown to be locally and systemically activated in the acute phase and in a prolonged manner 131 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…This figure was adapted from [33] with permission from Wolters Kluwer Health, Inc. [54]. Many other studies reported the presence of D-dimer and FDP in not only cases of isolated head trauma [54,[56][57][58][59] but also torso trauma regardless of shock [6,12,16]. Furthermore, another investigation reported that hyper-fibrino(geno)lysis in severe head trauma is not directly related to shock [60].…”
Section: Coagulation Activation-induced Fibrino(geno)lysismentioning
confidence: 99%
“…In severe trauma, elevations in D-dimer and FDP levels are frequently observed and are complicated with coagulopathy, regardless of severe shock [6,12,16,[54][55][56][57][58][59]. Although severe head trauma is not generally complicated with shock, trauma-induced coagulopathy is frequently observed with this type of injury [54,[56][57][58].…”
Section: Coagulation Activation-induced Fibrino(geno)lysismentioning
confidence: 99%